Comparative democratic politics : a guide to contemporary theory and research - Keman, Hans (SAGE, 2002)
Democracy is the most widely used way of organizing politics in the contemporary world. Comparative Democratic Politics brings together a team of renowned international scholars to provide a comprehensive review of theory and research in this essential area of comparative study.